Correlation between Lecturer Support and Student Satisfaction: Insights from Blended English for Tourism Course - Antari, Addinda Maulidita; Kurniawan, Eri (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study investigates the relationship between hospitality students’ perceptions of lecturer support and their satisfaction with the English for Tourism course delivered in a blended learning format in response to the changing learning environments following the COVID-19 pandemic. Amid increasing demands for technology-integrated instruction in English for Specific Purposes (ESP), this research highlights the role of pedagogical support in shaping student satisfaction.Method – Employing a quantitative correlational approach, this study collected data using validated instruments: the Scale of Perceived Instructor Support (SPIS) and the ESP Student Satisfaction Scale. Out of 92 students enrolled in the course, 47 (51.1%) participated voluntarily. Pearson’s correlation coefficient was applied to examine the relationship between perceived lecturer support and student satisfaction. Findings – Results indicated that students perceived moderate to high levels of support from their lecturers and reported a generally positive experience with the course, as reflected in a strong positive correlation (r=0.732, p < 0.01) between lecturer support and student satisfaction, emphasizing the importance of lecturer presence, interpersonal connection, and responsive feedback in blended ESP instruction. Research Implications – The study contributes to the growing literature of ESP pedagogy and blended learning by affirming the crucial role of lecturer support in shaping positive student experiences. The research is limited by its single-institution scope, modest sample size, and insufficient examination of factors affecting students’ willingness to continue learning in blended format. Future research is recommended to investigate lecturer support’s impact on student motivation, psychological challenges, and learning outcomes, using longitudinal or mixed methods approaches.